Effect of Using a Cardiac Catheterization Table-Stabilizing Stick on the Quality of Cardiopulmonary Resuscitation in the Cardiac Catheterization Laboratory: A Simulation-Based Study. (1st August 2019) - Yamada, Tsuyoshi; Ito, Morihiro; Urai, Hisako; Ueda, Yumiko; Maki, Hiroaki; Baba, Reizo
Abstract : Rapid defibrillation and high-quality cardiopulmonary resuscitation (CPR) are necessary for patients with cardiopulmonary arrest, one of the most serious and frequently encountered complications in cardiac catheterization laboratories. However, when the catheterization table is withdrawn from its neutral position for fluoroscopy, it is unstable and unsuitable for resuscitation because of its cantilever structure. To stabilize the table in its withdrawn position, the use of a table-stabilizing stick might improve CPR quality. To investigate the effect of using a cardiac catheterization table-stabilizing stick on CPR quality, a CPR simulation mannequin was placed on a cardiac catheterization table that was withdrawn from the C-arm of the X-ray machine. CPR quality was assessed with or without the use of a table-stabilizing stick under the table. The CPR quality assessment (Q-CPR) scores were 79.6 ± 11.4% using the table-stabilizing stick and 47.7 ± 30.3% without the use of the stick device (p = 0.02). In this simulation-based study, the use of a table-stabilizing stick in a cardiac catheterization table withdrawn from the C-arm of the X-ray machine improved the quality of CPR.